Household food production and dietary diversity in a remote, former socialist society: Panel data evidence from Tajikistan - Takeshima, Hiroyuki; Lambrecht, Isabel B.; Akramov, Kamiljon T.; Ergasheva, Tanzila (SAGE Publications, 2025)
Background Despite a growing interest in household-level agriculture–nutrition linkage, evidence remains thin in countries like Tajikistan, one of the poorest former socialist countries where food crop production decisions by individual farm households had been significantly regulated by the government until recently. Objectives We narrow this knowledge gap by examining the linkages between households’ food production practice as well as their productivity performances and dietary diversity scores (DDS) of both the household and individual women in Tajikistan. Methods We use a panel sample of households and individual women of reproductive ages in the Khatlon province of Tajikistan, the poorest province and a major agricultural region of the country. Difference-in-difference propensity score regressions and panel fixed-effects instrumental variable regressions are applied. Results Higher overall diversity in food groups (FGs) produced by households, as well as greater overall production per land and per household member at the household level, leads to higher DDS both for the household and for individual women, particularly in areas with poor food market access. FG-specific analyses suggest that for vegetables, fruits, legumes/nuts/seeds, dairy products, and eggs, significant one-on-one linkage exists between own production and consumption for these FGs. Conclusions Results underscore the importance of supporting household-level agricultural diversification and agricultural productivity growth in Tajikistan to improve dietary diversity, especially in remote areas.